A contrastive study of discourse markers used by native and Chinese L2 English speakers across speech context. (16th March 2017) - Liu, Binmei
Abstract : Discourse markers (DMs) are difficult even for advanced L2 speakers compared with L1 speakers because of their special linguistic features. The influence of contextual factors on the use of DMs has not been examined in detail in the literature. The present article investigates the impact of speech contexts (interview vs conversation) on the use of DMs by native and advanced Chinese speakers of English. Data for the study were gathered using individual sociolinguistic interviews and group conversations. A quantitative analysis revealed that native English speakers used and and just more frequently in the interviews than in the conversations at a significant level; the Chinese speakers of English used oh, ok, and uh huh significantly more often in the conversations than in the interviews. A qualitative analysis showed that the functions of well varied across the contexts by both groups. The article further analyses the reasons for these differences: they can be due to different functions of individual markers across contexts or influence of L2 speakers' native language (Mandarin Chinese), etc. The results indicate that the advanced L2 English speakers may not have acquired some DMs used by the native English speakers in terms of frequency and functions across the speech contexts. The article suggests that explicit instruction of functions of DMs which are difficult for L2 speakers of English can be strengthened in EFL/ESL (English as a foreign/second language) classrooms.